The relationship of internet addiction with self-esteem, attention, fear of missing developments, life satisfaction and personality traits - Çınar, Çağrı Yalçın; Mutlu, Elif (Journal of Dependence, 2019)
Objective: The aim of this study was to determine the level of Internet addiction in university students and to examine the factors associated with internet addiction.Method: The sample consists of 400 participants, 265 female and 135 male, studying in Kırklareli University in 2016-2017 academic year. Personal information form, Addiction Profile Index Internet Form, Rosenberg Self-Esteem Scale, Fear of Missing Out Scale, Life Satisfaction Scale, Adult Attention Deficit Hiperactivity Disorder Self-Report Scale and Five Factor Personality Scale had been used as a measurement devices.Results: 16.5% of the participants were internet addicts. The most preferred social media accounts are respectively Instagram (%84), Facebook (%81) and Snapchat(%56.75).Conclusion: Internet dependency score was found low in this study. However, It was determined that FoMO, attention deficit, hyperactivity and neurotic personality trait have positively associated with internet addiction. It was determined that there is a negative relationship between self-esteem, life satisfaction and responsibility and internet addiction.
Keywords: Internet addiction; fear of missing out; self-esteem